Análise de um curso de especialização em saúde mental na modalidade educação a distância - SÁ, Ivonice Siqueira de (2019)
This research examines a course of a specialization course in mental health in the distance learning modality, which was offered by UNA-SUS/UFMA in 2011. The study aimed to know the profile of the student who finished its course, identify the main mental health topics addressed in the Term Papers and compare the distribution of newly trained professionals in the cities where the course was accomplished. This research is part of the project Technical Cooperation for the Production of Learning and Innovation Objects in DL for SUS Professionals: an exploratory study on teaching and learning in courses offered to health professionals in the DL modality. We performed a descriptive, quantitative and qualitative research. Data collection took place from August 2018 to May 2019, in three stages: TP data and abstract descriptors were obtained from the UNA-SUS/UFMA Monitoring Center, while data on work, education, age, gender, marital status, training and work experience in mental health were collected in the enrollment forms and the binding data were collected in the National Register of Health Facilities. The quantitative analysis was performed calculating frequency, mean and standard deviation using the Stata® 14 software, while the qualitative analysis frequency and word order with Open EVOC software (Ensemble de Programmes Permettant l' Analyse des Evocations). Most newly trained were women, nurses and had no mental health training until the date of enrollment. There was a high turnover of workplaces among the newly trained when comparing the years 2011 and 2019, where a large number of professionals are outside the job market. The main TP descriptors that compose the central core of the analysis of the four houses were: mental disorder, mental health and depression. The descriptors of the second periphery that complement the central core were: Mental Health Care Network and Primary Health Care. The contexts presented in the TP confirms the frequency of mental disorders, the need for networking and the importance of APS, the high turnover evidenced, as well as many graduates outside the labor market brings reflection on the need for new mental health training for SUS professionals, because there is no evidence that the professionals who took over the municipalities are qualified for this assistance.